(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Adolescent Idiopathic Scoliosis (AIS) is a three-dimensional (3D) deformity of the spine that can occur in children aged 9 and older. It is more commonly found in girls. This paper presents an ergonomic flexible girdle or brace design for preteen and teenage girls who have early scoliosis with a spinal curve that is less than 20 degrees, which reduces the chances of further aggravation of their scoliosis by exerting corrective forces onto their torso and improving their posture. During the design and development process, it was found that the key factors that affect the efficiency of the flexible girdle are the design and fit of the garment, corrective force mechanism employment, material selection and application, and aesthetic and convenience of the product that affect compliance. The results of ergonomic design process in this project can be applied to related product development projects in the future and used as reference for doing so.